Technology Venture Blueprint ROI Enterprise HOVERBOARD "S" / Muhammad Rozaimie Rosli - Rosli, Muhammad Rozaimie (2020)
ROI Enterprise offers a new innovation product call the Hoverboard “S”. It is smart scooter comes with different features from electronic scooter in the market. Our product is very practical and effective to be use especially by students. The design and style of our product is according to the current trend and meet the demand. We offer superior quality and design at affordable prices. Our products will continue evolve based on the consumer trends and demands.